[OA023] Multiparametric MRI measurements of renal perfusion and oxygenation. (August 2018) - Haddock, Bryan; Larsson, Henrik; Andersen, Ulrik
Abstract : Purpose: Renal medullary flow abnormalities have been implicated in the pathogenesis of primary and secondary hypertension. Still, due to the difficulties involved, combined measurements of medullary perfusion and oxygenation have only recently been reported. Using MRI, we have measured changes in renal flow, perfusion and oxygenation in healthy humans during activation of the sympathetic nerve system and after injection of a diuretic. Methods: We measured changes in renal perfusion and blood oxygenation in 10 healthy subjects during handgrip exercise (HGE) and after furosemide injections on two occasions in a 3 Tesla MR-scanner. For the two interventions, renal arterial flow (RAF) data were acquired using phase contrast (PC-MRI), perfusion using arterial spin labeling (ASL) and changes in blood oxygenation were monitored using both T 2 ∗ measurements and blood oxygenation dependent (BOLD) imaging. Results: HGE induced a decrease of RAF by 17.4 ± 7%, and an increase of oxygenation with a Δ T 2 ∗ of 22 ± 9% in the renal medulla despite a significant drop in medullary perfusion (−12 ± 5%). In the renal cortex on the other hand, both perfusion and oxygenation decreased significantly. After furosemide injection, mean T 2 ∗ values in the renal medulla increased by 45% (p < 0.01) while other parameters, including medullary perfusion, did not change significantly. Coefficients of variation (CV) between baseline measures between the two scanning days were 6.6% for renal artery flow. T 2 ∗ and ASL perfusion in renal cortex had CV values of 4.2%, 5.1%, and 6.4% and 11.2% respectively in the medulla. Conclusion: Measurements of RAF, BOLD and perfusion in renal cortex and medulla were acquired for the first time in healthy subjects during hand-grip testing and furosemide injection. Measurements from both interventions reveal that while changes in RAF, cortical perfusion and cortical oxygenation were synonymous, medullary oxygenation increased independently of perfusion after a diuretic injection and contrary to decreased perfusion during HGE induced sympathetic activation. These techniques may be useful in pathophysiologic studies of patients with hypertension or renal artery stenosis, and a better understanding of the mechanisms regulating medullary oxygenation.